Integrating Sufi Education into Judicial Ethics: Strengthening Integrity among Religious Court Judges in Indonesia - Galib, Andi Muhammad; Matlail Fajar, Abbas Sofwan; Kholish, Moh. Anas (Pustaka Peradaban, 2025)
This study addresses the challenge of maintaining integrity and judicial ethics in Indonesia’s Religious Courts, which are often threatened by social, political, and economic pressures. In response to the modern crisis of spirituality, Sufi education offers a prophetic paradigm that emphasizes purification of the soul, honesty, and justice as divine orientations. This research, based on library study of classical and contemporary Sufi literature alongside legal regulations on judicial ethics, argues that Sufi education provides a spiritual foundation for strengthening judges’ moral integrity and professional ethics. The findings reveal that the internalization of teachings such as tazkiyat al-nafs, muraqabah, and ihsan can enhance ethical awareness, foster judicial independence, and reduce the risk of abuse of authority. Rather than replacing formal codes of ethics, Sufi education complements them with a deeper spiritual framework. The study recommends integrating Sufi educational modules into judicial training and continuous professional development. Its novelty lies in framing Sufi education not merely as private spirituality but as an institutional instrument for building a clean, dignified, and just Religious Court system in Indonesia. Penelitian ini membahas tantangan menjaga integritas dan etika peradilan di Pengadilan Agama Indonesia yang kerap terancam oleh tekanan sosial, politik, dan ekonomi. Di tengah krisis spiritualitas modern, pendidikan tasawuf menawarkan paradigma profetik yang menekankan pensucian jiwa, kejujuran, dan keadilan sebagai orientasi ilahiah. Dengan menggunakan metode studi pustaka terhadap literatur tasawuf klasik dan kontemporer serta regulasi hukum terkait kode etik hakim, penelitian ini menegaskan bahwa pendidikan tasawuf dapat menjadi fondasi spiritual untuk memperkuat integritas moral dan etika profesional hakim. Temuan menunjukkan bahwa internalisasi ajaran seperti tazkiyat al-nafs, muraqabah, dan ihsan mampu meningkatkan kesadaran etis, menumbuhkan independensi peradilan, dan meminimalisasi potensi penyalahgunaan kewenangan. Pendidikan tasawuf tidak dimaksudkan menggantikan kode etik formal, melainkan melengkapinya dengan kerangka spiritual yang lebih mendalam. Penelitian ini merekomendasikan integrasi modul pendidikan tasawuf dalam pelatihan calon hakim maupun pengembangan profesional berkelanjutan. Kebaruan penelitian terletak pada argumentasi bahwa pendidikan tasawuf bukan sekadar urusan spiritualitas privat, tetapi juga instrumen institusional untuk membangun peradilan agama yang bersih, bermartabat, dan berkeadilan.